(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract The popular online shopping platforms have attracted a lot of attention in recent years. The researchers have emphasized how crucial online platforms are to marketing since they can directly affect customers’ purchasing decisions because they can be perceived by consumers prior to consumption. This idea has been expanded in a variety of ways, from the physical to the virtual marketplace, with the growth of online shopping. When consumers access almost all shopping platforms, the idea of "service" expands from its conventional meaning and increasingly includes other novel conceptual elements. However, as online purchasing grows, it becomes more challenging to determine what high standards should apply to online shopping platforMs. to thoroughly investigate the potential applications of online shopping platforms in order to support effective purchasing behavior. after finishing the study, it is stated that the marketing strategy of sellers is the first reason why students recognize to use online platforms to purchase an item, and price is a huge contribution to students preference in buying product as they prefer a product that is more affordable and more achieving for their budget, and product quality is one of the reason why students tend to buy more on online shopping and use online platforms and also one of the reason why the students stop purchasing is when they experience poor product quality. Knowing what to consider first before using online platforms to buy a product is effective for a better shopping experience and achieving satisfaction in the shopping experience of buyers. Knowing what first to consider when using an online platform to purchase will make the person a wise consumer.